Effect of Turkey Berry (Solanum torvum Swartz) on Cholesterol, Hemoglobin, and Leukocyte Levels of Rabbits with Atherogenic Diet ol, Hemoglobin (Hb) and Leukocyte Levels in Rabbits with Atherogenic Diet - Nur Rahman; Khairuddin; Yohanes Kristianto; Ibnu Fajar; Faisya Raihanah; Karina Muthia Shanti (Indonesian Journal of Human Nutrition, 2025)
Atherosclerosis is likely to cause oxidative stress due to an imbalance between free radicals and antioxidants that results in decreased hemoglobin and leukocyte levels and increased cholesterol in the blood. Turkey berry (Solanum torvum) has the potential to overcome these problems. This study aimed to analyze the effect of turkey berry administration on cholesterol, hemoglobin, and leukocyte levels in rabbits. The research used a Completely Randomized Design (CRD) using 30 rabbits fed an atherogenic diet for five weeks. The results showed that turkey berry administration has a significant effect on cholesterol levels (p<0.05). Supplementation with 60 mg/kg BW/day of turkey berry powder in the atherogenic diet reduced cholesterol more effectively than the 40 mg/kg BW/day dose. The inclusion of turkey berry to an atherogenic diet increased the hemoglobin levels (p>0.05); the average hemoglobin level was 12.9 ± 0.09 g/dL across all groups. Although the effect of turkey berry powder on raising hemoglobin was more significant in rabbits on a normal diet, its administration in rabbits fed an atherogenic diet successfully decreased average cholesterol levels to 219.42 mg/dL and caused a slight increase in average leukocyte levels to 8.655. In conclusion, turkey berry supplementation lowered cholesterol levels, had a minimal effect on leukocyte counts, and did not significantly influence hemoglobin levels in rabbits fed an atherogenic diet.